2004
DOI: 10.1249/01.mss.0000113478.92945.ca
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness, Injuries, and Team Performance in Soccer

Abstract: Coaches and medical support teams should pay more attention to jump and power training, as well as preventive measures and adequate rehabilitation of previous injuries to increase team success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
326
4
58

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(421 citation statements)
references
References 17 publications
33
326
4
58
Order By: Relevance
“…The results of the present study showed that the goalkeepers were significantly (p<0.02) taller (172.40 cm) than the other players, whereas midfield players proved to be the shortest (167.28 cm). Similar results were reported by the previous researcher Carter 29 ; Matkovic et al 30 ; Arnason et al 31 ; Gil et al 11 . Tall players tend to have an advantage in certain playing positions and, therefore, are oriented towards these roles, notably in goalkeeping and defense.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the present study showed that the goalkeepers were significantly (p<0.02) taller (172.40 cm) than the other players, whereas midfield players proved to be the shortest (167.28 cm). Similar results were reported by the previous researcher Carter 29 ; Matkovic et al 30 ; Arnason et al 31 ; Gil et al 11 . Tall players tend to have an advantage in certain playing positions and, therefore, are oriented towards these roles, notably in goalkeeping and defense.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, a significant relationship has been demonstrated between team success and average jump height and leg extension power, thus demonstrating the importance of this physical component for soccer-specific performance [60]. There are numerous reports within the literature detailing the power performance of female players across differing competition levels; university [37,41,42], high school [56,61], lower division domestic league [32,44], higher division domestic [20,21,35], national team youth [36] and senior national team players [11,36,43,49].…”
Section: 6)mentioning
confidence: 99%
“…Injury occurrence notably, results in decreased player availability and subsequent non-participation in match-play potentially impacts on team performance although contradictory observations exist (Árnason et al, 2004;Dauty & Collon, 2011;Eirale, Tol, Farooq, Smiley, & Chalabi, 2013;Hägglund et al 2013). The association between squad management, player availability and injury and success in professional soccer therefore warrants further attention.…”
Section: Introductionmentioning
confidence: 99%